2022
DOI: 10.1001/jamanetworkopen.2022.26327
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Survival and Comorbidity Burden Between Asian and Native Hawaiian and Other Pacific Islander Patients With Cancer

Abstract: ImportanceImproper aggregation of Native Hawaiian and other Pacific Islander individuals with Asian individuals can mask Native Hawaiian and other Pacific Islander patient outcomes. A comprehensive assessment of cancer disparities comparing Asian with Native Hawaiian and other Pacific Islander populations is lacking.ObjectiveTo compare comorbidity burden and survival among East Asian, Native Hawaiian and other Pacific Islander, South Asian, and Southeast Asian individuals with non-Hispanic White individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 16 publications
4
14
0
Order By: Relevance
“…Asian and Hispanic patients were found to have better survival outcomes in our study, which agrees with the findings from other studies . Many Asian individuals have lower body mass index and fewer comorbidities, which are known to be protective mediators in breast cancer mortality . Asian patients are reported to have higher ERBB2 + disease, which has a good response to NACT, and may be another reason for their improved survival .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Asian and Hispanic patients were found to have better survival outcomes in our study, which agrees with the findings from other studies . Many Asian individuals have lower body mass index and fewer comorbidities, which are known to be protective mediators in breast cancer mortality . Asian patients are reported to have higher ERBB2 + disease, which has a good response to NACT, and may be another reason for their improved survival .…”
Section: Discussionsupporting
confidence: 91%
“…[15][16][17] Many Asian individuals have lower body mass index and fewer comorbidities, which are known to be protective mediators in breast cancer mortality. 17,18 Asian patients are reported to have higher ERBB2 + disease, which has a good response to NACT, and may be another reason for their improved survival. 15 Pan et al 19 found that Asian patients with breast cancer tumors have higher immune scores and higher levels of CD8 + T cells, macrophages, and cytotoxic natural killer cells, which suggest improved response to immunotherapy and better survival outcomes.…”
Section: Chemosensitivitymentioning
confidence: 99%
“…For example, minoritized populations have difficulty participating in trials given the mismatch in trial eligibility and these populations' disease stages, comorbidity burden, and other clinical characteristics 18,19 . This is concerning for Indigenous populations, such as the NHPI population, who are known to have greater burden of comorbidities and thus may be disproportionately excluded from clinical trial opportunities 20 . In another prospective study of 171 patients considered for participation in a clinical trial, only half had a potential trial opportunity available, given their cancer diagnosis and stage of disease 21 .…”
Section: Patient-level Considerations and Solutionsmentioning
confidence: 99%
“…2 However, NHPI patients with cancer continue to be underrepresented in oncology clinical trials and face even more significant health care disparities than AA patients with cancer, including worse outcomes and survival rates. 7 Although AAs are the fastest growing population in the United States, over the past three census data, funding for research remains low at only 0.17% of the total NIH-funded research from 1992 to 2018. 3,8,9 While funding for the overall AA & NHPI population is low, the difference is even more stark when the NHPI population is examined separately from AA populations.…”
mentioning
confidence: 99%
“…2 However, NHPI patients with cancer continue to be under-represented in oncology clinical trials and face even more significant health care disparities than AA patients with cancer, including worse outcomes and survival rates. 7…”
mentioning
confidence: 99%